Challenge for rural financial intermediaries: the case of the state of Guerrero - Ruiz, Noemi Lezama; Villagomez Mendez, Juan; Lezama Hernández, Lino Gerardo (Revista Mexicana de Ciencias Agrícolas, 2022)
Rural financial services have a dynamic character with challenges to defy related to their ability to adapt and stay in the rural sector, being credit a trigger for rural development and the opportunity to increase local competitiveness, the National Finance of Agricultural, Rural, Forestry and Fisheries Development with the vision of increasing productivity and contributing to improve the standard of living of the population identifies rural financial intermediaries as strategic allies. The objective of this research is to identify the elements that give certainty to the permanence of rural financial intermediaries that work with funds from the National Finance of Agricultural, Rural, Forestry and Fisheries Development. The research used an individual questionnaire, for its approach, a cross-sectional observational study was designed, with a sample of 96 borrowers whose information was processed in the SPSS23 program with an analysis of contingency tables, in 2019. The results show that the state of Guerrero contributes 3.68% of the credit placement nationwide, with the simple credit (63%) being the one with the highest placement, 31% is through RFIs, in the case that is analyzed, it was identified that the female gender and those with the marital status of married are those that show greater certainty of payment and only 26 % were borrowers for the first time, the credit placed is refactionary, being the nature of the product, a credit focused on economic and productive growth, finally the perspective of inter-institutional work manages to streamline response times and transfer credit conditions to the final borrower.